Design and Analysis of a Single and Double Stator of Single-Phase Slot-Less Permanent Magnet Generator - Masruni, Norafiza (2009)
Permanent magnet (PM) generator has been an object of numerous research studies with different structures and geometries proposed for different applications. Generator is a machine that is used to convert mechanical energy into electrical energy. Due to the availability and decreasing cost of high energy PM material, PM generator is more attractive than other types of power generator. For agriculture application, the existing generator that is available in the market does not meet the size and power capability requirements. The proposed PM generator operates in a single-phase, slot-less type, and the flux direction in the air gap is radial. The PM generator was developed for agriculture application especially for high speed performance between 3000 revolution per minute (rpm) to 8000 rpm. The prime mover for this PM generator is a petrol engine with capability of 1.3 horse power (hp). The external force from the engine will make the generator rotates with high speed. The electrical power produced energizes an electric motor suitable for pruner application. Thus, in this research, the design and analysis of the PM generator is studied. The PM generator is aimed to produce an output voltage of 130 V with the overall diameter size of 104 mm. At the early stage, a single-phase slot-less PM generator is designed with a single stator and the PM is placed in the v-shape pattern to provide the required flux. Based on the flux distribution in the PM generator, it shows that about half of the upper flux goes to the air gap and travel in the stator while the other bottom half goes to the shaft. This means that half of the bottom flux is wasted at the shaft. According to this characteristic, a double stator slot-less PM generator is proposed with a circular pattern PM with air gap between the inner and outer stator to improve the performance of the generator. Based on this design, all the generated flux is used to generate the voltage. In order to understand the conditions where the PM generator shows potential advantages, various parameters are varied such as number of pole and radius of the rotor. Generally, the technique used to examine the performance of the PM generator is permeance analysis method (PAM) and finite element method (FEM). The theoretical analysis is verified by comparing the predicted and measured output power, resistance, and inductance on a prototype of the PM generator. Based on the results, the highest output power could be achieved by single stator slot-less PM generator with diameter of 104 mm at speed of 3000 rpm is equal to 110 W when it has 6-pole with rotor radius of 36 mm. On the other hand, the double stator slot-less PM generator could produce 200 W at speed of 3000 rpm when it has 8-pole and rotor height of 22 mm.